Lipopolysaccharide induces platelet activation in HIV patients: the role of different viral load patterns - Nocella, Cristina; Mezzaroma, Ivano; Cammisotto, Vittoria; Castellani, Valentina; Milito, Cinzia; Rugova, Alban; Frati, Giacomo; Pignatelli, Pasquale; Violi, Francesco; Pastori, Daniele; Carnevale, Roberto (HIV medicine, 2021)
Objectives This study aimed to assess whether gut‐derived lipopolysaccharide (LPS) could affect platelet function in HIV‐1 patients with residual viral load. Methods In 23 HIV‐1 patients on effective antiretroviral treatment, 10 treatment‐naïve HIV‐1 subjects and 20 healthy subjects (HS), LPS, zonulin, markers of platelet activation and oxidative stress were evaluated. In vitro, platelets from HS were exposed to plasma from HIV‐1‐infected treated and untreated patients. Results Compared with HS, LPS was higher in treated and treatment‐naïve subjects with HIV‐1 (7.7 ± 2.9, 80.9 ± 13.7 and 75.3 ± 22.6 pg/mL, P < 0.001 vs. HS) as well as serum zonulin (1.3 ± 0.5, 6.1 ± 1.5 and 5.3 ± 1.7 ng/mL, P < 0.001 vs. HS). LPS and zonulin were correlated in HIV patients (Spearman correlation coefficient (rS) = 0.73, P < 0.0001). Levels of soluble CD40 ligand (sCD40L), soluble P‐selectin (sP‐selectin) and thromboxane B2 (TxB2) were higher in HIV‐1‐treated and treatment‐naïve subjects compared with HS as well as NADPH oxidase 2 (NOX2) activation and hydrogen peroxide (H2O2) production. In vitro, sCD40L, sP‐selectin and TxB2 production, NOX2 activation and p47phox phosphorylation were higher in platelets exposed to plasma from HIV‐1 patients with different viral load compared with the exposure to plasma from HS. This effect was blunted in platelets pre‐treated with TLR4 or TLR7 inhibitors. Conclusions Low‐grade endotoxaemia and persistent viraemia increase platelet function with a mechanism mediated by NOX2 in patients with HIV‐1 infection.